FACTORS RELATED TO UTILIZATION OF JAMKESMAS IN PRIMARY HEALTH CARE AT JAMBI, INDONESIA 2011 - Theresia Rhabina Noviandari Purba (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Jamkesmas was public health insurance organized by the Indonesian government that aims to ensure the health needs of the poor. Jamkesmas organized to increase the coverage of the poor who cannot access health services. This study aimed to examine the factors associated with utilization Jamkesmas in primary health care.This study is a quantitative research which uses cross sectional design. 100 respondents were selected by random sampling. Method of administration is face-to-face structured interview.The results show 54% people used Jamkesmas in primary health care. According to the result of statistical analyses, factors related to utilization of Jamkesmas in primary health care are accessibility (p= 0.0005) and supports from family and health workers (p=0.0005). In order to increase utilization of Jamkesmas, people need supports from their family and health workers to using primary health care. Health workers, such as doctor and nurse, have to increase quality of services to make patient more comfortable and build trust between doctor and patient. Easier accessibility, included distance, time, cost of transportation, are also needed to increase utilization.Keywords:Jamkesmas, utilization, primary health care